Cost effectiveness analysis of antenatal HIV screening in United Kingdom. Issue 7219 (6th November 1999) - Ades, A E; Sculpher, M J; Gibb, D M; Gupta, R; Ratcliffe, J
Abstract: Objective: To assess the cost effectiveness of universal antenatal HIV screening compared with selective screening in the United Kingdom. Design: Incremental cost effectiveness analysis relating additional costs of screening to life years gained. Maternal and paediatric costs and life years were combined. Setting: United Kingdom. Main outcome measures: Number of districts for which universal screening would be cost effective compared with selective screening under various conditions. Results: On base case assumptions, a new diagnosis of a pregnant woman with HIV results in a gain of 6.392 life years and additional expenditure of £14 833. If decision makers are prepared to pay up to £10 000 for an additional life year, this would imply a net benefit of £49 090 (range £12 300-£59 000), which would be available to detect each additional infected woman in an antenatal screening programme. In London, universal antenatal screening would be cost effective compared with a selective screening under any reasonable assumptions about screening costs. Outside London, universal screening with uptake above 90% would be cost effective with a £0.60 HIV antibody test cost and up to 3.5 minutes for pretest discussion. Cost effectiveness of universal testing is lower if selective testing can achieve high uptake among those at higher risk. A universal strategy with only 50% uptake may not be less cost effective in low prevalence districts and may cost more and be less effective than a well run selective strategy. Conclusions: Universal screening with pretest discussion should be adopted throughout the United Kingdom as part of routine antenatal care as long as test costs can be kept low and uptake high.